Профілактика інтернет-залежності співробітників - Росовецька, Ніна Василівна (Ірпінь, 2025)
У кваліфікаційній роботі теоретично узагальнено феномен інтернет-залежності з позицій системного підходу, що дозволило подолати фрагментарність існуючих напрацювань з даної проблеми та отримати наукові дані про психологічні особливості осіб з інтернет-залежністю; розширено наукове уявлення про детермінанти виникнення та розвитку інтернет- залежності особистості; обґрунтовано, що психологічні особливості інтернет-залежності визначаються рівнем її сформованості й проявляються у якісній своєрідності психологічних властивостей та виборі стратегій поведінки співробітників. У результаті дослідження виявлено, що психологічні особливості інтернет-залежності визначаються рівнем її сформованості й проявляються у якісній своєрідності психологічних властивостей та виборі стратегій поведінки співробітників. Встановлено взаємозв’язок між показниками інтернет-залежності співробітників ресторанного та їх схильності до різних видів залежності, а також загальної залежності. Виявлено, що психологічні комплекс особистісних корелятів інтернет-залежних молодих фахівців і досвідчених співробітників не мають істотних відмінностей. Розроблено процедуру діагностики та програму профілактики інтернет-залежності у співробітників ресторанного підприємства. Подальшого вивчення набули типологічні характеристики інтернет-залежності співробітників сфери ресторанного бізнесу.

The qualification work theoretically summarizes the phenomenon of Internet addiction from the standpoint of a systemic approach, which allowed us to overcome the fragmentation of existing developments on this problem and obtain scientific data on the psychological characteristics of individuals with Internet addiction; the scientific understanding of the determinants of the emergence and development of Internet addiction of a person has been expanded; it has been substantiated that the psychological features of Internet addiction are determined by the level of its formation and are manifested in the qualitative uniqueness of psychological properties and the choice of behavioral strategies of employees. The study revealed that the psychological characteristics of Internet addiction are determined by the level of its formation and are manifested in the qualitative uniqueness of psychological properties and the choice of behavioral strategies of employees. The relationship between the indicators of Internet addiction of restaurant employees and their tendency to various types of addiction, as well as general addiction, has been established. It has been found that the psychological complex of personal correlates of Internet-addicted young professionals and experienced employees do not have significant differences. A diagnostic procedure and a program for the prevention of Internet addiction among restaurant employees have been developed. The typological characteristics of Internet addiction among restaurant business employees have been further studied.
Keywords: профілактика; інтернет-залежності; співробітники; адикція; internet; addiction; determinants; prevention; employees